Victimological Perspectives on Factors That Contribute to Elder Abuse: A Case Study of Mount Frere Town in Umzimvubu Local Municipality, Eastern Cape, South Africa (Global Journal of Human-Social Science, 2021)
The aim of this study was to explore factors contributing to elder abuse in Mount Frere Town, at Umzimvubu Local Municipality in the Eastern Cape. A qualitative approach was used in the study, with purposive sampling to select 14 participants. The data was obtained through focus group interviews. Thematic analysis was used to analyse data and interpret results. The cornerstone of this study was based on theories to generate critical questions and also make contributions to the existing knowledge. The Routine Activity theory by Cohen and Felson and the Lifestyle/Exposure model were used to direct this study. Results revealed that the elderly people were not getting enough support or protection from government structures, such as the Criminal Justice and the Department of Social Development.
Keywords: caregiver; elderly; abuse; offender; protection; victimisation